Responses of chlorophyll fluorescence parameters of the facultative halophyte and C-3-CAM intermediate species Mesembryanthemum crystallinum to salinity and high irradiance stress - Broetto, Fernando; Duarte, Heitor Monteiro; Luettge, Ulrich (Elsevier B.V., 2007)
Mesembryanthemum crystallinum L. (Aizoaceae) is a facultative annual halophyte and a C-3-photosynthesis/crassulacean acid metabolism intermediate species currently used as a model plant in stress physiology. Both salinity and high light irradiance stress are known to induce CAM in this species. The present study was performed to provide a diagnosis of alterations at the photosystem 11 level during salinity and irradiance stress. Plants were subjected for up to 13 days to either 0.4M NaCl salinity or high irradiance of 1000 mu mol m(-2) s(-1), as well as to both stress factors combined (LLSA = low light plus salt; HLCO = high light of 1000 mu mol m(-2)s(-1), no salt; HLSA = high light plus salt). A control of LLCO = low light of 200 mu mol m(-2) s(-1), no salt was used. Parameters of chlorophyll a fluorescence of photosystem 11 (PSII) were measured with a pulse amplitude modulated fluorometer. HLCO and LLSA conditions induced a weak degree of CAM with day/night changes of malate levels (Delta malate) of similar to 12 mM in the course of the experiment, while HLSA induced stronger CAM of Delta malate similar to 20mM. Effective quantum yield of PSII, Delta F/F'(m), was only slightly affected by LLSA, somewhat reduced during the course of the experiment by HLCO and clearly reduced by HLSA. Potential quantum efficiency of PSII, F-v/F-m, at predawn times was not affected by any of the conditions, always remaining at >= 0.8, showing that there was no acute photoinhibition. During the course of the days HL alone (HLCO) also did not elicit photoinhibition; salt alone (LLSA) caused acute photoinhibition which was amplified by the combination of the two stresses (HLSA). Non-photochemical, NPQ, quenching remained low (< 0.5) under LLCO, LLSA and HLCO and increased during the course of the experiment under HLSA to 1-2. Maximum apparent photosynthetic electron transport rates, ETRmax, declined during the daily courses and were reduced by LLSA and to a similar extent by HLSA. It is concluded that A crystallinum expresses effective stress tolerance mechanisms but photosynthetic capacity is reduced by the synergistic effects of salinity and tight irradiance stress combined. (c) 2006 Elsevier GmbH. All rights reserved.
Keywords: C-3-photosynthesis; chlorophyll fluorescence; crassulacean acid metabolism; irradiance; malate accumulation; Mesembryanthemum crystallinum; salinity